Identification and Characterization of an RNA-Dependent RNA Polymerase Activity within the Nonstructural Protein 5B Region of Bovine Viral Diarrhea Virus - Zhong, Weidong (American Society for Microbiology, 1998)
Nonstructural protein 5B (NS5B) of bovine viral diarrhea virus (BVDV) contains sequence motifs that are predictive of an RNA-dependent RNA polymerase activity. We describe the expression and purification of the BVDV NS5B protein derived from an infectious cDNA clone of BVDV (NADL strain). BVDV NS5B protein was active in an in vitro RNA polymerase assay using homopolymeric RNA or BVDV minigenomic RNA templates. The major product was a covalently linked double-stranded molecule generated by a “copy-back” mechanism from the input template RNA. In addition, a nucleotide-nonspecific and template-independent terminal nucleotidyl transferase activity was observed with the BVDV NS5B preparation.